Strategi pemanfaatan energi terbarukan dalam rangka kemandirian energi daerah provinsi kalimantan timur - Heyko, Eduardo; Hasid, Zamruddin; Priyagus, Priyagus (INOVASI, 2016)
This research is aim to find out hotchpotch of East Kalimantan Province energy at 2025 after optimize renewable energy (biodiesel, bioethanol, and biogas) and to find out the most proper of renewable energy to developed by applying correct development strategy. This research use secondary data processing of taken spanning year time on 2002-2012. Renewable energy development strategy analysis conducted by using IFE and EFE matrix and also SWOT matrix. Whereas, projection analysis of energy necessity untill year 2025 conducted by using time series forecasting pursuant to method of trend analysis plot, smoothing plot, and decomposition plot. Software used to conduct forecasting is Minitab 16 Version. Result of research indicate that the fuel energy consumption in East Kalimantan Province at 2025 reach 47.970,20 thousand BOE, so the correct strategy to be used related to the utilization of renewable energy is conservative (self correction) strategy. Besides that, this optimization of utilization of renewable energy make East Kalimantan Province as self-supporting area of energy or Autonomous Energy Region with fossil energy savings which substituted by renewable energy is equal to 30.287,42 thousand BOE or 63,14% from regional energy necessity, wherein the most proper renewable energy to developed are biodiesel and biogas because they are more profitable than bioethanol.Keywords: Bioenergy, Renewable Energy, Development Strategy